Bowl-Shaped Carbon Nanobelts Showing Size-Dependent Properties and Selective Encapsulation of C70 - Lu, Xuefeng; Gopalakrishna, Tullimilli Y; Han, Yi; Ni, Yong; Zou, Ya; Wu, Jishan (Journal of the American Chemical Society, 2019)
The synthesis of carbon nanobelts (CNBs) with well-defined size and structure remains a challenging topic in nanocarbon chemistry and materials science. Herein, we report the synthesis, physical characterization, and supramolecular properties of two fully conjugated bowl-shaped CNBs (CNB1/CNB2), in which six/eight cyclopenta-rings are fused onto a macrocycle containing three/four alternately linked 2,7-pyrenyl and 2,7-phenanthryl units. The existence of five-membered rings results in a bowl-shaped geometry, as revealed by X-ray crystallographic analysis and density functional theory calculations. Both molecules contain an alternate aromatic phenanthrene-co-quinoidal pyrene structure to satisfy Clar’s aromatic sextet rule. The smaller size CNB1 has a deeper bowl depth (d = 4.997 Å) than CNB2 (d = 3.682 Å) and cannot undergo bowl-to-bowl (BTB) inversion below 373 K in toluene. However, the larger size CNB2 shows a smaller BTB inversion barrier (∼12 kcal/mol) at the coalescent temperature (248 K), which was estimated by variable-temperature NMR measurements. Both compounds exhibit a small energy gap and amphoteric redox behavior with multiple redox waves. The dications of CBN1 and CBN2, and the tetracation of CBN2, are experimentally accessible by chemical oxidation with NO·SbF6, all displaying unusual open-shell singlet diradical character with a small singlet–triplet energy gap (ΔE S–T = −2.71 kcal/mol for CBN1 2+ , −2.50 kcal/mol for CBN2 2+ , and −2.00 kcal/mol for CBN2 4+ ). The dications are globally aromatic while the tetracations are globally antiaromatic according to NMR measurements and theoretical calculations (anisotropy of the induced current density, nucleus independent chemical shift, and 2D isochemical shielding surface). The small bowl-shaped CNB1 demonstrates selective encapsulation of fullerene C70 over C60, with a large association constant (K a = 8.066 × 105 M–1 in toluene). However, the larger size CNB2 does not exhibit any encapsulation with both C60 and C70.